2017
DOI: 10.1371/journal.pone.0173536
|View full text |Cite
|
Sign up to set email alerts
|

Radiological features of primitive neuroectodermal tumors in intra-abdominal and retroperitoneal regions: A series of 18 cases

Abstract: ObjectivesTo characterize the imaging and clinicopathological features of primitive neuroectodermal tumors (PNETs) arising in intra-abdominal and retroperitoneal regions.MethodsEighteen patients with histopathologically proven intra-abdominal and retroperitoneal PNET were enrolled; computed tomography was performed for all cases, and magnetic resonance imaging was performed for a single case. Typical computed tomography and magnetic resonance imaging findings, including morphology, texture and enhancement feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(31 reference statements)
0
5
2
Order By: Relevance
“…The median age ranged from 1 (19) to 36 (25) years. A male preponderance was described in 14 studies (8,(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26). Nevertheless, there were a comparable 43 males and 46 females in the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The median age ranged from 1 (19) to 36 (25) years. A male preponderance was described in 14 studies (8,(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26). Nevertheless, there were a comparable 43 males and 46 females in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Peripheral PNETs are generally large, soft tissue masses with a reported mean diameter >5 cm, as confirmed by the reviewed studies that investigated primary tumor size (11,14,16,21,22,25,26). Tumor bulk was the single most important prognostic factor, with 80% survival among patients with smaller primary tumors (<100 ml), compared with only 40% survival among those with larger tumors (>100 ml) (27).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They also found that contrast-enhanced computed tomography revealed multiple feeding arteries within the masses and mild ring enhancement in several cases they examined. They believe these imaging features may be characteristic of intra-abdominal and retroperitoneal neuroectodermal tumors [13]. Mild ring enhancement was observed in 40% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, PNETs located peripherally typically express high amounts of the MIC2 antigen (CD99) [ 7 ] . However, recent updates have suggested heterogeneity in retroperitoneal PNET presentation, which is a combination of a pPNET with non-differentiated retroperitoneal sarcomas [ 8 ]. Hence, the ambiguous and vague presentation of the disease contributes to a complicated diagnosis.…”
Section: Introductionmentioning
confidence: 99%